DENTAL MANAGEMENT OF PATIENTS WITH ALZHEIMER’S DISEASE - DR. M.P.SANTHOSH KUMAR M.D.S. (International Journal of Pharma and Bio Sciences, 2015)
Alzheimer’s disease (AD), is the most common cause of dementia in adult life and is associated with the selective damage of brain regions and neural circuits critical for memory and cognition. However, the pathogenesis of this disease is complex and involves many molecular, cellular and physiological pathologies. Dental health problems in Alzheimer’s patients can lead to pain, unmanageable behaviour and extensive dental treatment. The clinical features, pathophysiology, medical management, dental findings and management of Alzheimer’s patients in dental office have been discussed in this review.